Satu Negara Satu Tujuan: Menyoal Konsep Negara Khilâfah Taqî Al-dîn Al-Nabhânî - Umar Faruq (Universitas Islam Negeri Mataram, 2005)
Taqî al-Dîn al-Nabhânî, an Islamic fundamentalist, with his political party Hizb al-Tahrîr al-Islâm, offered an idea of khilâfah. As a universal nation, which is aimed at providing solutions to the whole problems (final solution), is a political ideology in form covered by religious issue that is universality of Islam. This idea is based on the universality of Islam which has no boundary limit so as the Islamic political system is universal and its implementation to build a khilâfah state should also be universal and absolute. This ideological reason is supported by empirical reason addressed to the countries and nations perceived as disbelievers institutions applied to Islamic nations. Since the world order nowadays is built on the interaction among countries and nations world wide, to show Islamic supremation, the secularistic system must be replaced. The alternative solution offered by Taqî al-Dîn is khilâfah state where Allah is the Judge. Although the functions of representative authority conduct are, the same as those in the theocratic system, the khilâfah nation is claimed to be different from theocracy for historical reasons; there is no historical and ideological relationships between theocracy and Islamic politic. The khalîfah is not an incarnation of God as claimed by an emperor in a theocratic nation. Khalîfah is just a representation of God who is the same as ordinary person in the eye of God. The existence of khalîfah is to facilitate the implementation of Allah’s rules, as the owner and the holder of the authority. The claim that khalîfah is the implementer of Allah’s rules and representation of God, practically, resembles the religious and political functions in a theocratic system. Therefore, khilâfah state is not an expression of religion ressurection, but merely a statement of new order to replace the present system with the khilâfah system claimed to be the religious principles.